Pullout Interaction Mechanism of Geogrid Strip Reinforcement. Issue 4 (1st January 1995) - Watanabe, K.; Alfaro, M.C.; Miura, N.; Hayashi, S.
Abstract : Soil-reinforcement interaction parameters used in the design of reinforced soil systems are typically evaluated by measuring pullout resistance. A combined two-dimensional and three-dimensional interaction mechanism is proposed to evaluate the pullout resistance of geogrid strip reinforcement embedded in dense granular soil. Pullout tests were conducted using uniaxial geogrid reinforcement of various specimen widths. Results from the pullout tests confirmed that a three-dimensional interaction mechanism had developed at both edges of the strip reinforcement. This interaction mechanism is caused by a confinement of the dilating zone of soil around the reinforcement as described by Schlosser and Elias (1978). For the type of geogrid reinforcement and backfill material used in this investigation, the combined interaction mechanism is applicable for a strip reinforcement width, B, greater than 20 cm. For strip reinforcement with B less than 20 cm, the influence of restrained soil dilatancy results in the development of a purely three-dimensional interaction mechanism across the strip reinforcement width.